2021
DOI: 10.3390/jcm10112358
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota–Gut–Brain Axis and Alzheimer Disease. From Dysbiosis to Neurodegeneration: Focus on the Central Nervous System Glial Cells

Abstract: The microbiota–gut system can be thought of as a single unit that interacts with the brain via the “two-way” microbiota–gut–brain axis. Through this axis, a constant interplay mediated by the several products originating from the microbiota guarantees the physiological development and shaping of the gut and the brain. In the present review will be described the modalities through which the microbiota and gut control each other, and the main microbiota products conditioning both local and brain homeostasis. Muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 199 publications
(276 reference statements)
0
17
0
Order By: Relevance
“…A growing body of evidence suggests the hypothesis that the microbiota–gut system can be thought of as a single unit that interacts with the brain via the microbiota–gut–brain axis. Through this axis, a constant interplay mediated by several products originating from the microbiota guarantees the physiological development and shaping of the gut and the brain ( 43 , 44 ). We evaluated gut microbiome diversity and calculated the relative abundances of each group at all kinds of classification level, especially at the level of phylum and genus, to find the changes in the intestinal microbiota structure of different groups.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests the hypothesis that the microbiota–gut system can be thought of as a single unit that interacts with the brain via the microbiota–gut–brain axis. Through this axis, a constant interplay mediated by several products originating from the microbiota guarantees the physiological development and shaping of the gut and the brain ( 43 , 44 ). We evaluated gut microbiome diversity and calculated the relative abundances of each group at all kinds of classification level, especially at the level of phylum and genus, to find the changes in the intestinal microbiota structure of different groups.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance in the functions of microglia and astrocytes is also related to the augmentation of extracellular glutamate, which is related to the neuron excitotoxicity resulting from the overactivation of the N-methyl-D-aspartate receptors (NMDA). Besides that, in the neuroinflammation scenario, astrocytes and microglia lose their capacity to release cytokines related to neuron survival and functioning [112,[117][118][119].…”
Section: Ginkgo Biloba and Mild Cognitive Impairmentmentioning
confidence: 99%
“…Several neurodegenerative diseases, such as Alzheimer’s disease (AD), have been posited to be related to gut microbiota composition. For example, it has been suggested that gut microbiota may modulate amyloid-β accumulation, alter blood–brain barrier permeability, and induce neuroinflammation via its metabolites [ 51 , 52 ]. In fact, several microbiota species, such as enterobacteria, can secrete amyloid protein curli, which accelerate amyloid polymerization and create potent immunogenic complexes that activate immune cells [ 49 ].…”
Section: The Role Of Gut Microbiota and Its Metabolites In Brain Functioning And Neurodegenerationmentioning
confidence: 99%